2014
DOI: 10.1111/jmwh.12170
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed‐Methods Study on Factors Influencing Prenatal Weight Gain in Ethnic‐Minority Women

Abstract: Strategies identified in this study such as providing focused education directed at nonpregnant nulliparous women, stressing portion control, helping women better manage their cravings, and providing more pragmatic support and resources need to be explored in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 41 publications
(69 reference statements)
6
20
1
Order By: Relevance
“…In addition, the women in this study did not eat foods that did not taste good to them, which is consistent with other studies that reported taste is an important factor in dietary choices . Women reported their taste preferences had changed during pregnancy, similar to women in other studies who were not interested in eating food that did not taste good to them; even if they thought they should for the baby …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, the women in this study did not eat foods that did not taste good to them, which is consistent with other studies that reported taste is an important factor in dietary choices . Women reported their taste preferences had changed during pregnancy, similar to women in other studies who were not interested in eating food that did not taste good to them; even if they thought they should for the baby …”
Section: Discussionsupporting
confidence: 89%
“…These included sweet, spicy, savory, and fast foods. The tendency to crave such foods is consistent with the findings of other studies . Findings from a qualitative study of 21 African American women by Reyes et al were slightly different: The pregnant women in this study indicated they ate whatever they craved but also decreased their intake of fast food and nutrient poor foods because of their desire for a healthy newborn and in response to heartburn symptoms .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Unfortunately, more than two thirds of pregnant women gain in excess of these recommended guidelines (Moore Simas et al, 2008). Most low-income women report not receiving advice on how much weight to gain during pregnancy (Hackley, Kennedy, Berry, & Melkus, 2014; Phelan et al, 2011). …”
Section: Content Of Prenatal Carementioning
confidence: 99%